ASSIGNMENT OPTIMIZATION OF WARSHIPS TO SUPPORT ELEMENTS AT THE SEA NORTH NATUNA - Prasetyo, Budi; Vanany, Iwan; Prabowo, Ayip Rivai (JOURNAL ASRO, 2022)
Base limitations in implementing fuel oil support and security demands in the North Natuna Sea waters security operation sectors require an analysis of the optimal distribution of fuel support, in order to minimize operating fuel costs so that the support is timely, effective, and on target in the title of warship operations in securing the working area of the North Natuna Sea. The current problem is that in the working area of Lantamal A, there is no overall support system for refueling at the wharves to support operations in the waters of the North Natuna Sea, so warship elements operating in the waters of the North Natuna Sea can only fill up fuel at the Lantamal A Tanjung pier. Pinang, Lanal Batam and Lanal Ranai. Therefore, real steps are needed to overcome this problem. Because this will not only reduce efficiency and effectiveness but also cause a void for warship elements operating in the waters of the North Natuna Sea. By using the Linear Programming method to determine the warship operating sector in the North Natuna Sea and the Center of Gravity (CoG) method to determine the position of KRI B in optimizing the ability to distribute fuel to KRI elements in the North Natuna Sea waters operation sector so as to obtain efficiency fuel consumption of 17.36% (2,789,565 liters). Keywords: Linear Programming, Center of Gravity, Fuel Distribution, Operations, North Natuna Sea.